Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Karyawan pada Kantor Bupati Simalungun - Damanik, Jhon Cristmas; Raya Panjaitan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Employee performance is a key factor in achieving organizational goals, especially in government institutions such as the Simalungun Regent's Office. This study aims to analyze the influence of transformational leadership style and organizational culture on employee performance. The research uses an associative quantitative approach with a population of all employees of the Simalungun Regent's Office, totaling 50 people, taken as a census sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that transformational leadership and organizational culture have a positive and significant effect partially and simultaneously on employee performance. The coefficient of determination (R²) of 0.612 indicates that the two independent variables contribute 61.2% to the variation in employee performance. The practical implication of this research is the need for leaders to consistently apply transformational leadership and strengthen an organizational culture oriented toward performance and public service. This research can be a reference for human resource development in local government environments.